Total Phenolic Fraction (TPF) from Extra Virgin Olive Oil: Induction of apoptotic-like cell death in Leishmania spp. promastigotes and in vivo potential of therapeutic immunomodulation. - Kalliopi Karampetsou; Olga S Koutsoni; Georgia Gogou; Apostolis Angelis; Leandros-Alexios Skaltsounis; Eleni Dotsika (Public Library of Science (PLoS), 2021)
Background Leishmaniasis is a serious multifactorial parasitic disease with limited treatment options. Current chemotherapy is mainly consisted of drugs with serious drawbacks such as toxicity, variable efficacy and resistance. Alternative bioactive phytocompounds may provide a promising source for discovering new anti-leishmanial drugs. Extra Virgin Olive Oil (EVOO), a key-product in the Mediterranean diet, is rich in phenols which are associated with anti-inflammatory, anti-cancer and anti-microbial effects. In this study, we investigate the anti-leishmanial effect of Total Phenolic Fraction (TPF) derived from EVOO in both in vitro and in vivo systems by investigating the contributing mechanism of action. Methodology/principal findings We tested the ability of TPF to cause apoptotic-like programmed cell death in L. infantum and L. major exponential-phase promastigotes by evaluating several apoptotic indices, such as reduction of proliferation rate, sub-G0/G1 phase cell cycle arrest, phosphatidylserine externalization, mitochondrial transmembrane potential disruption and increased ROS production, by using flow cytometry and microscopy techniques. Moreover, we assessed the therapeutic effect of TPF in L. major-infected BALB/c mice by determining skin lesions, parasite burden in popliteal lymph nodes, Leishmania-specific antibodies and biomarkers of tissue site cellular immune response, five weeks post-treatment termination. Our results show that TPF triggers cell-cycle arrest and apoptotic-like changes in Leishmania spp. promastigotes. Moreover, TPF treatment induces significant reduction of parasite burden in draining lymph nodes together with an antibody profile indicative of the polarization of Th1/Th2 immune balance towards the protective Th1-type response, characterized by the presence of IFN-γ-producing CD4+ T-cells and increased Tbx21/GATA-3 gene expression ratio in splenocytes. Conclusions/significance TPF exhibits chemotherapeutic anti-leishmanial activity by inducing programmed cell death on cell-free promastigotes and immunomodulatory properties that induce in vivo T cell-mediated responses towards the protective Th1 response in experimental cutaneous leishmaniasis. These findings enable deeper understanding of TPF's dual mode of action that encourages further studies.